Sanitation indicators as a tool to evaluate a food safety and sanitation training program for farmstead cheese processors. (August 2017) - Machado, Robson A.M.; Cutter, Catherine N.
Abstract: This project evaluated the impact of a food safety and sanitation training program, developed for farmstead cheesemakers, by investigating its effects on the cleanliness of cheesemaking rooms of dairy farms in Pennsylvania. Participating farms (n = 16) were divided randomly into control (n = 6; no training) and two treatments, consisting of a food safety and sanitation training program without a video vignette (treatment 1; n = 5) and a training program supplemented with a video vignette (treatment 2; n = 5). Before the training and again 3–4 months after the training, environmental samplings were conducted on select surfaces in cheesemaking rooms. Surfaces were swabbed and evaluated for aerobic bacterial counts (AC), Enterobacteriaceae (EB), yeast and molds (YM), Listeria spp., and for levels of adenosine triphosphate (ATP). The results demonstrate that the training program, with or without the video vignette, significantly reduced ( p < 0.05 ) populations (log10 CFU/100 cm 2 ) of AC (treatment 2 = 1.23), EB (treatment 1 = 1.18; treatment 2 = 0.89), and ATP (treatment 1 = 0.41; treatment 2 = 0.61) in samples taken from floors and drains. The results from this study may serve as a reference for future evaluations of food safety-related training programs that look beyond changes in employee knowledge, attitudes, skills, or behavior, and address or correlate to other potential indicators of sanitation, such as microbial counts and ATP levels. Highlights: Food safety training for small dairy farmers is paramount for cheese safety. Evaluation of a food safety training program using hygiene indicators is proposed. The training affected sanitation indicators. This study may serve as a guide for using microbiological data in program evaluation.